A Review: Replication Strategies for Big Data in Cloud Environment - A. Fazlina, M.; Latip, Rohaya; Ibrahim, Hamidah; Abdullah, Azizol (International Journal of Engineering and Technology, 2018)
Big Data technology is emerging around the globe to provide better insight and decision making for every organization. As the nature of Big Data is providing variety and huge volume of data with complex data computation, cloud environment is the best choice to resolve storage issues. However, the challenge remain in this technology is data availability due to heterogeneity of Big Data systems. Data must be always accessible and available for user regardless of time. The most essential option to satisfy this desire is providing best replication strategies which able to afford business continuity without interruption. Hence, this paper delivers better perceptions on the data replications strategies for Big Data systems in cloud environment. Critical review concerning replication strategies is discussed and presented with imperative details from numerous researchers. Additionally, this work contributes thorough discussion on advantages and gaps for each study. This study also explores algorithms and performance metrics that has been improved by researchers. The methodology used to conduct this paper was using qualitative research approach. Ultimately, this paper would be helpful for future researchers in understanding and selecting the best strategy to fit their research scope and goals. Â Â